Ecojustice and Education : a Special Issue of educational Studies - Wayne, Kathryn Ross, 1951-; Wayne, Kathryn Ross (Routledge, Taylor and Francis, 2014)
First Published in 2004. Routledge is an imprint of Taylor & Francis, an informa company.